How The Image of The Company and The Value of The Customer Affect Satisfaction - Octafian, Ray; Mochamad Miswanto Gunawan; Krisnawati Setyaningrum Nugraheni; Septiana Raihan Saputri (Brilliant International Journal Of Management And Tourism, 2022)
A primary goal of this study is to investigate and dissect the connection between a company's public image and its ability to retain satisfied clients. The second objective is to investigate the connection between customer value and contentment. Third, to dissect what factors have the most impact on happiness and why. The description of each variable answer in this study is Corporate Image (X1), Customer Value (X2) and Customer Satisfaction (Y1) can be done by means of descriptive analysis In accordance with the results of the discussion there are several things that can be concluded in accordance with the objectives of this study there is a positive influence of corporate image variable on customer satisfaction, the better the corporate image that is formed with the existing suitability it will form customer satisfaction. There is a positive influence of the customer value variable on customer satisfaction, the more customers benefit from the programs offered, the more customer satisfaction increases. The customer value variable is the variable that has the biggest influence on customer satisfaction, so it needs special attention for management to improve customer satisfaction.